PERAN GIZI SEIMBANG DALAM PENCEGAHAN STUNTING PADA ANAK 4-6 TAHUN - Rosida Rosida; Rachma Hasibuan (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
The purpose of this study is to identify the role of balanced nutrition in preventing stunting among children aged 4-6 years, focusing on the steps taken by schools to prevent stunting in children aged 4-6 years at TK Al Hikmah Ketapang Banyuwangi. This research uses a qualitative approach with descriptive statistics. The subjects of the study are children aged 4-6 years at TK Al Hikmah Ketapang Banyuwangi. Data collection techniques include observation, interviews, and documentation. Observations were conducted directly by observing the activities of providing supplementary food at TK Al Hikmah Ketapang Banyuwangi. Interviews were conducted with the principal and one parent. Documentation involved collecting photos or other documents that support this research. The data analysis technique used data triangulation, which consists of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the "Rabu Sehat Bermutu" program and the provision of supplementary food at TK Al Hikmah Ketapang Banyuwangi are effective steps in preventing stunting and supporting children's growth and development. This program also raises parental awareness of the importance of balanced nutrition, fosters healthy eating habits, and contributes to the development of a healthy and high-quality generation